ChemInform Abstract: A Novel Organic—Inorganic Hybrid Sandwich‐Type Germanotungstate with Discrete [Fe4(en)2 (α‐GeW9O34)2]8‐ Polyoxoanions and 1‐D [Fe4(en)(α‐GeW9O34)2] n8n‐ Polymeric Chains. Issue 32 (18th July 2013) - Tian, Shuanbao; Li, Yanzhou; Zhao, Junwei; Ma, Pengtao; Chen, Lijuan
Abstract The new compound [enH2]8 [Fe4(en)(α‐GeW9O34)2] [Fe4(en)2 (α‐GeW9O34)2] ·en·14H2O is hydrothermally synthesized from a mixture of K8Na2[A‐α‐GeW9O34], Ce(NH4)4(SO4)4, FeCl3, en, and H2O (autoclave, 160 °C, 6 d, 25% yield).